Institutional Model of Decentralization in Action - Iwan J. Azis (Asian Development Bank (ADB), 2011)
Applying the Institutional Model of Decentralization, the paper argues that the presumption that local democracy will impose accountability pressure on elected officials does not always hold. Even in a democratic system like in Indonesia, decentralization policy is welfare-enhancing only for the developed regions, not for all, exacerbating interregional welfare disparity. This "captured democracy" is largely due to the presence of "negative local capture". Where welfare has not improved, limited participation, low initial welfare combined with poor quality of local leaders are found to be the most critical determinants.
hdl:11540/1989
Keywords: 330; Dezentralisierung; Bürgerbeteiligung; Demokratisierung; Indonesien